A Novel Technique for Image Authentication in Frequency Domain Using Discrete Fourier Transformation Technique (IAFDDFTT) - Ghoshal, Nabin; Mandal, Jyotsna Kumar (Malaysian Journal of Computer Science, 2008)
In this paper a novel technique for Image Authentication in Frequency Domain using Discrete Fourier Transformation Technique (IAFDDFTT) has been proposed to authenticate a gray level PGM, TIFF image by embedding a message/image where 2 x 2 submatrix is taken as source matrix from the image matrix and transform into the frequency domain. Two bits of authenticating message/image are fabricated within the real part of each pixel, excluding the first pixel of each submatrix where the position is chosen using a hash function. The process is repeated for each submatrix on row major order to insert authenticating message/image content and 128 bits Message Digest (MD-5), generated from authenticating message/image. Inverse DFT is performed to transform the embedded image from frequency to spatial domain as final step of encoding. The decoding is done through the reverse procedure. The experimental results against statistical and visual attack has been discussed and compared with the existing steganography algorithm like S-Tools. Histogram analysis, noise analysis, and standard deviation computation of source image with embedded image shows the better results in comparison with existing S-Tools.